GRANTED EXCEPTION DUE TO THE NEGATIVE STATEMENT IN PETITION AS AN EFFORT TO ENSURE LEGAL CERTAINTY IN INDONESIA: EKSEPSI SEBAGAI AKIBAT DARI PERNYATAAN NEGATIF DALAM PERMOHONAN SEBAGAI UPAYA UNTUK MENJAMIN KEPASTIAN HUKUM DI INDONESIA - Listyani, Ajeng Aditya; Antonius Sidik Maryono; Sanyoto (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
Dispute resolution through the courts is carried out by filing a lawsuit against the party. The lawsuit is filed with the intention of obtaining legal protection for the rights of one party and forcing the other party to fulfill their obligations after the mediation process has failed. The lawsuit has to fulfill the formal and material requirements, including the formulation of the petition. The petition should not have a negative sentences structure and have to meet the formal requirements for the drafting of a petition. A negative petition gives the other party the opportunity to file an exception of lawsuit. This research was normative juridical research with analytical descriptive specifications. This research used a statutory approach and a case approach. The data used was secondary data with primary and secondary legal materials obtained from literature studies. The primary legal material is laws and regulations. Secondary legal materials are in the form of literature. The data was collected by the literature study method. The data was presented with normative text and analyzed with qualitative normative methods to obtain conclusions. The results of the study show that for petition that have negative sentences structure, the defendant can file an exception to the lawsuit and the legal consequence is that the lawsuit is declared Niet Onvankelijke Verklaard.